Changes in salivary oxytocin in response to biologically-relevant events in farm animals: method optimization and usefulness as a biomarker - Moscovice, Liza R.; Sobczak, Birgit; Niittynen, Taru; Koski, Sonja E.; Gimsa, Ulrike (Frontiers in Physiology, 2024)
Although best known for its established role in mediating parturition and lactation, the highly-conserved neuropeptide hormone oxytocin also mediates a range of social and stress-buffering processes across mammalian species. Measurements of peripheral oxytocin in plasma have long been considered the gold standard, but there is increasing interest in developing methods to detect oxytocin non-invasively in saliva. Here we present an analytical and biological validation of a novel method to measure salivary oxytocin (sOXT) in an under-studied research group: farm animals. Given their similarities with humans in physiology and brain, methods that can identify valued social contexts and social relationships for farm animals and investigate their function have implications for clinical research as well as for animal welfare science. However, current methods to measure sOXT vary greatly in terms of sample collection, pre-measurement processing and measurement and more rigorous standardization and validation of methods is critical to determine the utility of sOXT as a biomarker of salient social events and related emotions. We optimized a method for extracting sOXT in pigs and horses and measured sOXT in extracted samples using a commercially available enzyme-immunoassay. Extracted samples were within acceptable ranges for precision (CVs < 15.2%), parallelism and recovery (94-99%) in both species. Salivary oxytocin increased in samples collected during birth in pigs (Friedmans, p = 0.02) and horses (Wilcoxon, p = 0.02). Salivary oxytocin tended to decrease in sows after a 90-min separation from their piglets (Wilcoxon, p = 0.08). We conclude that sOXT can be reliably linked to physiological events that are mediated by the oxytocinergic system in farm animals, but that more research is needed to determine whether sOXT is a reliable trait marker for more general oxytocin system activation in response to salient social events. Future research should characterize how individual attributes and salivary parameters influence sOXT measurement and should emphasize reporting of analytical and biological validations to increase acceptance of non-invasive methods.